1981
DOI: 10.1113/jphysiol.1981.sp013840
|View full text |Cite
|
Sign up to set email alerts
|

Electrotonic coupling in internally perfused crayfish segmented axons.

Abstract: SUMMARYWe have developed a technique for cannulation and internal perfusion of crayfish segmented lateral axons. Experiments on perfused and non-perfused axons lead to the following conclusions:1. Internally perfused segmented axons behave very similarly to non-perfused axons.2. The axial electrical resistance of the junctional region is almost as low as a comparable segment of axon.3. Neither intracellular Ca2+ nor H+ is effective in disrupting the intercellular communication pathway in perfused axons.On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 15 publications
(23 reference statements)
5
32
0
Order By: Relevance
“…2D). Octanol, a known gap-junction inhibitor (Johnston and Ramon, 1981), significantly reduced dye coupling in ATP-s cells (Fig. 3).…”
Section: Dye Couplingmentioning
confidence: 88%
“…2D). Octanol, a known gap-junction inhibitor (Johnston and Ramon, 1981), significantly reduced dye coupling in ATP-s cells (Fig. 3).…”
Section: Dye Couplingmentioning
confidence: 88%
“…C a 2ϩ might not always interact directly with gap junctions but rather via a cytoplasmic intermediate. The sensitivity to C a 2ϩ disappeared after internal perf usion of, for example, crayfish segmented axons but recovered when calmodulin was added (Johnston and Ramon, 1981;Arellano et al, 1988). Conditions favoring phosphorylation of the channel protein also increased the sensitivity to calcium in the same preparation (Arellano et al, 1990).…”
Section: Calcium and Hydrogen Ions As Modulators Of Gap Junctional Pementioning
confidence: 98%
“…Johnston and Ramon (1981) Peracchia et al (1981) suggested that the cytoplasmic intermediate is calmodulin, since a calmodulin inhibitor prevents gap junction crystallization and electrical uncoupling. Calmodulin is a known enzyme activator, so changes in the configuration of the tubules of the junctional membrane also may involve an enzyme located along the nexus.…”
Section: Implications For Intracellular Eventsmentioning
confidence: 99%